To transform the function \( f(x) = 3^x \) into the new function \( -f(3x-2) + 1 \), we can represent the steps we would take in this transformation. The operation is essentially the following:
- Start with \( f(x) = 3^x \).
- Substitute \( 3x - 2 \) into the function: \( f(3x - 2) = 3^{(3x - 2)} \).
- Apply the negative sign: \( -f(3x - 2) = -3^{(3x - 2)} \).
- Add 1: \( -3^{(3x - 2)} + 1 \).
Now, for your table, we'll fill it out step-by-step using the expressions provided, based on the order of operations we performed.
New Function:
\[ -f(3x-2) + 1 \]
Table:
| Step | Expression | Result (for a chosen value of x, e.g., \( x = 1 \)) | |------|------------|------------------------------------------------| | 1 | \(3^{(3x-2)}\) | \(3^{(3(1)-2)} = 3^{1} = 3\) | | 2 | \(-3^{(3x-2)}\) | \(-3^{(3(1)-2)} = -3^{(1)} = -3\) | | 3 | \(-3^{(3x-2)} + 1\) | \(-3 + 1 = -2\) |
Completed Table:
| Step | Expression | Result | |------|-----------------------------|--------| | 1 | \(3^{(3x-2)}\) | 3 | | 2 | \(-3^{(3x-2)}\) | -3 | | 3 | \(-3^{(3x-2)} + 1\) | -2 |
Note: The values in the "Result" column are specifically for \( x = 1 \). You can substitute any other value of \( x \) into the expressions to find different results.